Comparing policy routes for low-carbon power technology deployment in EU – an energy system analysis. (February 2017) - Simoes, Sofia; Nijs, Wouter; Ruiz, Pablo; Sgobbi, Alessandra; Thiel, Christian
Abstract: The optimization energy system model JRC-EU-TIMES is used to support energy technology R&D design by analysing power technologies deployment till 2050 and their sensitivity to different decarbonisation exogenous policy routes. The policy routes are based on the decarbonised scenarios of the EU Energy Roadmap 2050 combining energy efficiency, renewables, nuclear or carbon capture and storage (CCS). A "reference" and seven decarbonised scenarios are modelled for EU28. We conclude on the importance of policy decisions for the configuration of the low carbon power sector, especially on nuclear acceptance and available sites for new RES plants. Differently from typical analysis focussing on technology portfolio for each route, we analyse the deployment of each technology across policy routes, for optimising technology R&D. R&D priority should be given to those less-policy-sensitive technologies that are in any case deployed rapidly across the modelled time horizon (e.g. PV), but also to those deployed up to their technical potentials and typically less sensitive to exogenous policy routes. For these 'no regret' technologies (e.g. geothermal), R&D efforts should focus on increasing their technical potential. For possibly cost-effective technologies very sensitive to the policy routes (e.g. CSP and marine), R&D efforts should be directed to improving their techno-economic performance. Highlights: Policy routes for low-carbon power technology deployment in EU are compared. An analytical approach to compare technologies across scenarios is presented. The interplay between low-carbon power technologies is assessed. R&D priorities can be channeled to technologies rapidly deployed and less sensitive. Hydro and geothermal are the technologies less sensitive to the policy routes.